Shaping of Conditions for Raising the Level of Competition and Market Discipline in the Russian Banking Sector - Vilisova, Maria L.; Zaitseva, Ð¢atiana V.; Buryakov, Gennady A. (International Journal of Economics and Financial Issues, 2016)
The article reviews the main aspects of the impact of the state and legal instruments of banking business regulation on raising the level of competition and market discipline in the Russian banking sector. The basic concept of the state policy aimed at improving the competitiveness of the banking sector was defined; the basic results of changes in the level of competition both for the banking sector in general and for the stability of a particular banking institution were defined. The experience of foreign countries in shaping of the competitive and supervisory relationships in the banking sector was reviewed. Certain elements of this policy that should be adapted to the respective national practices were identified. International subjects of legal regulation of market discipline in the banking business, including Basel Committee on Banking Supervision, were reviewed. The characteristics of the regulatory requirements of the Basel Accords and peculiarities of their introduction into the banking sector were given. Recommendations on introduction of foreign experience in raising the level of competition and market discipline in the Russian banking sector were formulated. Keywords: Ð¡ompetition, merger, acquisition, banking sector, legal instruments of regulation JEL Classifications: G21, G28, O21